INNOVATION OF WEB BASED ENGLISH LEARNING MEDIA DEVELOPMENT - Siti Maesyaroh; Nida Amalia Asikin; Daswa Daswa (English Review: Journal of English Education, 2023)
SMP Negeri 1 Garawangi Kuningan is one of junior high schools that uses manual English learning media such as books and paper for learning evaluation. This manual learning system will raise many problems such as longer time consuming the assessment process, moreover, the use of books and paper allows tearing or damage, and it leads to teacher-centered learning process that can make students bored and reduce student learning interest. Therefore, innovation in the development of web-based English learning media for junior high school students is needed. This web-based innovation helps students to learn and understand English after school hours. The target achieved in this study is the production of English learning application that is interesting, easy to understand, and easy to use. This study uses a qualitative descriptive method because it is based on data from direct observation and the theoretical basis of learning media. Meanwhile, for the system development method, Extreme Programming that is consisting of 4 stages i.e., planning design, coding, and testing is used in the study. The result of this study shows that this application of English learning media is accepted to be used by students to learn English after school hours.